Effects of cerebral small vessel disease on the outcomes in cryptogenic stroke with active cancer - Ki-Woong Nam (Nature Portfolio, 2021)
Abstract Cerebral small vessel diseases (cSVDs) affect the prognosis of various types of ischemic stroke. Therefore, we evaluated the association between cSVD and the prognosis of cryptogenic stroke patients with active cancer. We enrolled patients diagnosed with cryptogenic stroke and active cancer from 2010 to 2016. Early neurological deterioration (END) was defined as a ≥ 2-point increase in the total NIHSS score or a ≥ 1-point increase in the motor NIHSS score within the first 72 h. We defined an unfavorable outcome as the modified Rankin Scale (mRS) score ≥ 3 points. We analyzed cSVD separately for each subtype including white matter hyperintensity (WMH), silent brain infarct (SBI), and cerebral microbleed (CMB). A total of 179 cryptogenic stroke patients with active cancer were evaluated. In the multivariable analysis, SBI was significantly associated with END (adjusted odds ratio = 3.97, 95% confidence interval: 1.53–10.33). This close relationship between SBI and END increased proportionally with an increase in SBI burden. However, WMH and CMB showed no significant association with END. None of the cSVD subtypes showed a statistically significant relationship with the 3-month unfavorable outcome. SBI was the only parameter closely associated with END in cryptogenic stroke patients with active cancer.